High expression of DDR1 is associated with the poor prognosis in Chinese patients with pancreatic ductal adenocarcinoma - Huo, Yanmiao (J Exp Clin Cancer Res, 2015)
BACKGROUND: Discoidin domain receptors 1 (DDR1), a subtype of DDRs, has been reported as a critical modulator of cellular morphogenesis, differentiation, migration and invasion. METHODS AND RESULTS: In this study, we investigated the expression of DDR1 and its clinical association in Chinese patients with pancreatic ductal adenocarcinoma (PDAC). Across a cohort of 30 patients, we examined DDR1 expression in paired PDAC and corresponding adjacent non-tumor tissues by real-time quantitative PCR (RT-qPCR), or western blotting. DDR1 expression is significantly higher in PDAC, as compared to normal adjacent tissue, confirming results from the Oncomine databases. We validated DDR1 expression by immunohistochemistry across a non-overlapping cohort of 205 PDAC specimens. Kaplan-Meier survival curves indicate that increased expression of DDR1 is associated with a poor prognosis in PDAC patients (P = 0.013). Multivariate Cox regression analysis identified DDR1 expression, age, N classification and liver metastasis as independent prognostic factors in PDAC. CONCLUSIONS: This study demonstrated that DDR1 can well serve as a novel prognostic biomarker in PDAC.